"Ripped Off" By the System: Housing Policy, Poverty, and Territorial Somatization in Regent Park Housing Project, 1951-1991 - Purdy, Sean (Labour/Le Travailleur)

(untitled) (Canadian Committee on Labour History, 2003)
Abstract Canada's oldest and largest public housing project, Regent Park in Toronto, was originally conceived as an ideal community for low-income families in housing hardship. By the 1990s, however, it had become virtually synonymous with socio-economic marginalization and behavioural depravity. Indeed, the broader social identity of Regent Park has become an accumulation and escalation of the stigma of its residents. The first section of this article charts the historical escalation of polarization between Regent Park residents and the Metropolitan Toronto population by comparing a series of broadly illustrative statistical traits over a 40-year period. This long-term historical perspective allows us to scrutinize the development of socio-economic marginalization both before and after the boom period of postwar capitalism from the 1940s to the 1970s. It confirms that Regent's resident population underwent a dramatic process of socio-economic divergence in comparison to the general Metropolitan Toronto population, which began in the mid to late 1960s before the onset of outright assaults on the welfare state. I flesh out the stark statistical portrayal by considering various qualitative sources such as oral testimony, letters to the author by former tenants, rare resident case files, and internal and public documents from the various housing authorities. In the second section, I explain the rise of socio-economic inequality. Contrary to currently popular underclass theories, I directly point the arrow of responsibility for rising poverty and inequality towards state housing policies, including wider urban renewal strategies and internal public housing practices, and neoliberal economic restructuring. Unlike most studies, I centre in a third section on the potently deleterious effects of stereotyping Regent Park as an outcast space. Stigmatizing renderings by external observers were not free-floating ideological representations but real reflections and shapers of spatial and social divisions with concrete economic and social consequences for tenants. I conclude by discussing what residents themselves thought about their homes and how they coped with stigmatization and material deprivation. Sometimes accepting and internalizing negative external representations and/or projecting these labels onto their neighbours and other times resolutely battling against these brutalizing depictions, Regent Park residents were always active players in building a meaningful living space.